Central diabetes insipidus: alert for dehydration in very low birth weight infants during the neonatal period. A case report - Ferlin, Maria Lúcia Silveira; Sales, Débora Simone; Celini, Fábia Pereira Martins; Martinelli Junior, Carlos Eduardo (São Paulo Medical Journal, 2015)
CONTEXT: Central diabetes insipidus (CDI) is a rare cause of hypernatremia during the neonatal period. The diagnosis is particularly difficult in very low birth weight (VLBW) newborns. CASE REPORT: We report on a preterm newborn who presented CDI soon after birth. On the third day of life, signs of dehydration were present despite normal fluid supply. The diuresis rate was 4.4 ml/kg/h. Although the fluid supply was then increased, the dehydration continued, with hypernatremia, normal glycemia, diuresis of 7.4 ml/kg/h and urine density of 1005 mOsmol/l. Thus, a diagnostic hypothesis of diabetes insipidus was raised. A test with a nasal vasopressin analogue (dDAVP) was performed and CDI was confirmed. Reduction of the fluid supply became possible through appropriate treatment. CONCLUSION: The diagnosis of CDI is rarely made during the neonatal period, especially in VLBW newborns, because of the difficulty in detecting elevated diuresis. Persistent hypernatremia, usually accompanied by hyperthermia despite abundant fluid supply, weight loss and low urine osmolality are important signs of alert.